49.5: True Glass‐based Micro‐display with 3µm pixel size using Deformed Helix Ferroelectric Liquid Crystal for VR/AR Displays. (26th August 2021) - Sun, Zhibo; Yuan, Zhengnan; Cheung, Alex; Shi, Runxiao; Kwok, Hoi-Sing; Srivastava, A. K.
Abstract : A glass‐based micro‐display with pixel size (<3µm) has been fabricated and verified in this work using deformed helix ferroelectric liquid crystal. High contrast (over 600:1), fast response time (< 400μs) and continuous gray scale within 5 V driving voltage are achieved in the prototype.